Pelatihan Pengoperasian dan Perawatan Mesin Pencacah bagi Komunitas Ciliwung Depok (KCD) sebagai Solusi Pengolahan Limbah Bambu Sungai Ciliwung - Syuriadi, Adi; Gun Gun Ramdlan Gunadi; Dianta Mustofa Kamal; Ahmad Bustomi; Andy Permana Rusdja; Muhamad Hanhan Nugraha (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
The problem of biomass waste, especially bamboo along the Ciliwung River, can pose significant environmental risks. Some ways to convert bamboo waste are making straw mushrooms or converting it into fuel through pyrolysis technology. Before being converted, this bamboo waste must be ground by chopping it in a chopper. This community service aims to improve the skills of participants from the Ciliwung Depok Community (KCD) regarding training in the operation and maintenance of waste shredder machines with a direct demonstration method and a grant of waste shredder equipment. The training was carried out for one day with 20 participants from KCD. Activities include delivering theories including socialization about biomass waste (garbage), waste sorting, management of its processing, then demonstration of tools/direct practice, and evaluation through pre-test and post-test. Data were analyzed using the Paired Two Sample for Means method. The training showed a significant increase in participants' knowledge and skills as evidenced by the difference in average pre-test and post-test scores which were statistically significant (p-value <0.05). The results showed that the training had a very big impact on the participants' abilities before and after the training. Similar programs are expected to be implemented in other communities to increase environmental awareness and the use of environmentally friendly technology. Keywords - Ciliwung, bamboo waste, chopper machine, training Abstrak Sampah adalah suatu bahan yang terbuang atau dibuang dari sumber hasil aktifitas manusia maupun alam yang belum memiliki nilai ekonomis. Pembuangan sampah yang tidak diurus dengan baik, akan mengakibatkan masalah besar. Demikian juga pembakaran sampah akan mengakibatkan pencemaran udara. Pembuangan sampah ke sungai (Ciliwung) akan mengakibatkan pencemaran air, tersumbatnya saluran air dan banjir. Dari permasalahan di atas, maka diperlukan sistem pengolahan sampah yang baik agar tidak terjadi kerusakan lingkungan dan juga diharapkan ada peningkatan ekonomi dari hasil pengolahan sampah tersebut. Tujuan dari kegiatan ini adalah memberikan pelatihan pengolahan sampah, terutama sampah dari bambu yang banyak dijumpai di aliran sungai Ciliwung. Pelatihan mencakup sosialisasi tentang biomassa/limbah biomassa (sampah), pemilahan sampah, manajemen pengolahannya dan pelatihan penggunaan alat pencacah sampah dengan metode demonstrasi langsung dan hibah alat pencacah sampah. Hasil dari kegiatan ini menunjukkan peningkatan pengetahuan masyarakat Komunitas Ciliwung Depok (KCD) tentang limbah biomassa, dalam mengolah limbah biomassa terutama bambu menjadi bio-pelet yang dapat digunakan sebagai bahan bakar. Penjualan bio-pelet ini diharapakan dapat meningkatkan perekonomian juga bagi masyarakat KCD. Kata kunci - Ciliwung, limbah bambu, mesin pencacah, pelatihan